BRAND IMAGE DAN BRAND PERSONALITY SERTA PENGARUHNYA TERHADAP BRAND LOYALTY PADA PRODUK PIKOPI DI PURWAKARTA - Kusumadewi, Ade Nurhayati Kusumadewi Nurhayati; Risma Ismawanti, Nurul; Mawardi, Amna; Wahyudi, Robby (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to determine the influence of brand image and brand personality on brand loyalty in Pikopi products in Purwakarta. Using a quantitative approach, data were collected from 97 respondents through a non-probability sampling technique. The data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the help of IBM SPSS 25. The results show that both brand image and brand personality have a positive and significant partial effect on brand loyalty. Simultaneously, these independent variables also have a significant effect, with an F value of 70.961 and a significance level of 0.000. The R square value of 0.602 indicates that 60.2% of the variation in brand loyalty can be explained by brand image and brand personality. In conclusion, brand image and brand personality play a crucial role in building consumer loyalty toward Pikopi products in Purwakarta